PENGARUH PENERAPAN MEDIA KUIS BERBASIS KAHOOT TERHADAP MINAT BELAJAR GEOGRAFI SISWA KELAS XI SMA NEGERI 1 SUNGAI PUAR KABUPATEN AGAM - Rahmat Hidayat; Afdhal Afdhal (JURUSAN GEOGRAFI FIS UNP, 2023)
This study aims to determine Interest in Learning Geography after using the kahoot application and the differences before and after using the kahoot application in class XI SMA Negeri 1 Sungai Puar, Agam Regency. This type of research uses a Quasi Experiment using only one class using a total sampling technique from class XI IPS 1. Data collection techniques use a questionnaire. The research respondent sample was measured using a Likert scale with a scale value category of 4. The results of the study can be concluded that: 1) there is an increase in students' interest in learning after using kahoot-based media. The average student interest in learning before using kahoot is 2.90 in the high category and the average student interest in learning after using kahoot is 3.21 in the very high category. 2) There is a difference in the effect of the kahoot-based quiz media before and after its application because the t-test is tcount 7.885 and the ttable is 2.036, so the tcount is greater than ttable at the 5% significance level, namely 7.885 > 2.036 while the N-Gain effectiveness level is 0.468 and is categorized as moderate.